2012
DOI: 10.1097/mpg.0b013e31824d970f
|View full text |Cite
|
Sign up to set email alerts
|

One‐step Percutaneous Gastrojejunostomy in Early Infancy

Abstract: In certain conditions that obviate the use of gastric feedings, the insertion of a jejunal feeding tube via gastrostomy constitutes an alternative to jejunostomy but requires a preexisting gastrostomy. Our aim was to assess a new technique of 1-step gastrojejunal tube insertion through a de novo gastrostomy. A total of 3 infants between 3 and 7 months old and weighing between 4.1 and 5.4 kg had a gastrojejunal feeding tube inserted using a 16-CH French introducer percutaneous endoscopic gastrostomy kit and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…However, parenteral nutrition rate significantly decreased from 54% to 17% of patients and a majority (70%) of patients were successfully transitioned to gastric feeding at endpoint. These results are better than most of previous studies which reported 7%–43% of successful transition to gastric feeding (7–11,13,15–18). As these reports did not study patients after GJT removal, the frequency of jejunal nutrition weaning could be underestimated.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, parenteral nutrition rate significantly decreased from 54% to 17% of patients and a majority (70%) of patients were successfully transitioned to gastric feeding at endpoint. These results are better than most of previous studies which reported 7%–43% of successful transition to gastric feeding (7–11,13,15–18). As these reports did not study patients after GJT removal, the frequency of jejunal nutrition weaning could be underestimated.…”
Section: Discussioncontrasting
confidence: 82%
“…GJTs were placed with endoscope-assisted technique with peroperative fluoroscopy following the previously reported technique (13). GJT placement was considered successful if its tip was distal to the third portion of the duodenum.…”
Section: Methodsmentioning
confidence: 99%
“…Although placement of a percutaneous endoscopic gastrostomy (PEG) followed by exchange for a GJ tube is the least invasive approach to obtain post-pyloric feeds, exchange must occur after the stoma matures, delaying the initiation of feeds by 6-8 weeks. [9][10][11] More recently, a variety of techniques for minimally invasive primary placement have evolved including percutaneous placement as well as the use of laparoscopy, fluoroscopy and endoscopy. These approaches allow for immediate feeding however they do not mitigate the common struggle to intubate the pylorus and prevent tube dislodgement during placement.…”
Section: Gastrojejunostomy Tube Placementmentioning
confidence: 99%
“…One-step GJT insertion through a de novo gastrostomy is a recent technique using the push technique. The procedure is basically the same as the 1-step percutaneous endoscopy button placement (76) where a neonatoscope is introduced through the 16-French introducer and passed into the jejunum via the pylorus and a GJT is placed over the guidewire as described above (77).…”
Section: Endoscopymentioning
confidence: 99%